Teologi Kritis dan Konseling Tauhid Integratif-Holistik: Rekonstruksi Epistemologi Kesehatan Mental Spiritual di Era Krisis Makna - Diva Indah Puspitasari; Nanda Ayu Rizwatun Ni'mah; Haikal Bustomi; Moh Fikri Muroqil Ubudiyah; Ali Hasan Siswanto (Indo Publishing, 2026)
The modern mental health crisis demonstrates that positivistic psychology and secular counseling approaches have not fully addressed the existential problems of contemporary humanity, particularly those related to the loss of meaning in life, spiritual alienation, and social disintegration. In many modern therapeutic practices, humans tend to be reduced to biological-psychological entities, while transcendent and spiritual dimensions are merely complementary elements. Research on spiritual counseling has indeed developed, but much of it remains adaptive to Western psychological theory and has yet to present an epistemological reconstruction based on the monotheistic worldview. This research gap lies in this study: the absence of a counseling paradigm formulation that integratively connects critical theology, Islamic psychology, and Sufism within a holistic-transformative framework. This study employs a critical theology approach and integrative-holistic monotheistic counseling with a qualitative, library-based research method through philosophical, theological, and psychological analysis of classical and contemporary literature. This study argues that monotheism functions not only as a normative doctrine but also as an epistemological paradigm capable of integrating spiritual, psychological, and social dimensions in the counseling process. This paradigm positions mental health as a unity between divine awareness, emotional regulation, spiritual purification, and social transformation. The scientific contribution of this research lies in the new formulation of Integrative-Holistic Tawhid Counseling as a model for reconstructing the epistemology of spiritual mental health. This paradigm broadens the horizons of contemporary Islamic psychology while simultaneously presenting a critique of the secular paradigm in modern counseling science.